1993
DOI: 10.1007/bf00182038
|View full text |Cite
|
Sign up to set email alerts
|

Preventable causes of male infertility

Abstract: The initial evaluation of the infertile man includes a diligent search for testicular factors, gonadotoxins, and coital factors so as to identify existing causes of impaired fertility and to prevent further dimunition in fertility. There are also prophylactic measures in the treatment of all men that can prevent future infertility, such as prompt correction of cryptorchidism, testicular torsion, genital infection, and adolescent varicocele and proper precautions to limit occupational, medical, and recreational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…Our results are remarkable, because there are a number of studies mentioned in the introduction that did find correlations or a negative effect from cigarette smoking and alcohol intake on semen parameters (Thompson, ; Chia et al ., , ; Goverde et al ., ; Vine et al ., ; Merino et al ., ; Hruska et al ., ; Wong et al ., ; Muthusami & Chinnaswamy, ; Okonofua et al ., ). An explanation could be that, according to a review by Vine (), an effect of smoking on semen parameters could be found between smokers and nonsmokers in fertile men, but this effect diminished as soon as infertile men were included in the analysis (Vine, ; Marinelli et al ., ).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our results are remarkable, because there are a number of studies mentioned in the introduction that did find correlations or a negative effect from cigarette smoking and alcohol intake on semen parameters (Thompson, ; Chia et al ., , ; Goverde et al ., ; Vine et al ., ; Merino et al ., ; Hruska et al ., ; Wong et al ., ; Muthusami & Chinnaswamy, ; Okonofua et al ., ). An explanation could be that, according to a review by Vine (), an effect of smoking on semen parameters could be found between smokers and nonsmokers in fertile men, but this effect diminished as soon as infertile men were included in the analysis (Vine, ; Marinelli et al ., ).…”
Section: Discussionsupporting
confidence: 50%
“…Studies also show biochemical alterations in semen due to smoking, such as increased reactive oxygen species activities and a decline in antioxidant molecules (Rubes et al ., ; Mostafa et al ., ; Kiziler et al ., ; Frey et al ., ; Soares & Melo, ). Multiple studies found negative effects on semen parameters, such as sperm density (Chia et al ., ; Vine et al ., ), total count (Vine et al ., ), motility (Thompson, ; Vine et al ., ), sperm morphology (Thompson, ; Chia et al ., ; Wong et al ., ) and semen volume (Vine et al ., ; Hruska et al ., ). One study found negative effects on all of these sperm characteristics due to cigarette smoke (Merino et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiologic causes and mechanisms of the HIV-associated AOH are likely multifactorial, and include (1) poor clinical or nutritional status, (2) use of certain prescription medications used to treat HIV, (3) illicit drugs including opiates and methadone, (4) pituitary dysfunction, (5) hepatitis C coinfection and other opportunistic infections, (6) advancing age and increasing length of time diagnosed with HIV, (7) changes in body composition, (8) increased levels of estradiol and increased levels of SHBG, (9) normal age-related declines, (10) low CD4 cell count, (11) high HIV viral load and disease progression, (12) lean body mass, (13) MetS, and (14) wasting lipodystrophy. [38][39][40][41][42][43][44][45][46] Adult-Onset Hypogonadism and Medication Effects Testosterone levels can be affected by many pharmacologic agents 47 that are frequently administered to or used by men (eg, opioids, glucocorticoids, cimetidine, tricyclic antidepressants, nicotine, and marijuana). Men who use high doses of anabolic steroids often find that their T levels fall to castrate levels after stopping these drugs.…”
Section: Adult-onset Hypogonadism and Human Immunodeficiency Virusmentioning
confidence: 99%
“…Concomitantly, the incidence of male infertility has been increasing in Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/envres industrial countries year after year, now affecting 25% of young men (Kumar and Singh, 2015;Thompson, 1993). The actual prevalence of male fertility leads to socio-economic changes in clinical management of infertile couples (Inhorn and Patrizio, 2015).…”
Section: Introductionmentioning
confidence: 98%